The Evolution of Branding: Navigating the New Landscape of Consumer Trust - Firman Syah Noor; Yongky Ade Prahasta; Hermanto Hermanto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the relationships between Brand Experience, Brand Communication Consistency, Brand Image, and Consumer Trust at PT. Indofood Jambi. Utilizing a quantitative approach with a sample of 100 consumers and employing SmartPLS for data analysis, the study examines how these variables interact to influence consumer trust. The findings reveal that Brand Experience significantly affects Brand Image, which in turn has a substantial impact on Consumer Trust. Brand Communication Consistency also plays a critical role, enhancing Consumer Trust through its positive effect on Brand Image. The results emphasize the importance of delivering exceptional brand experiences and maintaining consistent communication to build a strong Brand Image and foster Consumer Trust. These insights provide actionable recommendations for PT. Indofood Jambi to enhance customer loyalty and secure a competitive edge in the regional market.